Lopapeysa : the significance of patterns in the Icelandic sweater - Nykaenen, Lotta Kaarina, 1994- (2017)
The Icelandic sweater has a reputation of being “traditional” or “original”, even though the sweater’s history goes back only a bit over half a century. The sweater is usually recognized by its yoke and sleeve patterns that have also been seen in mainstream fashion, but how important are those patterns in defining the sweater? This thesis tracks the development of the Icelandic sweater’s patterns and finds out how much inspiration was drawn from neighbouring nations, including Greenland, Norway and Sweden. Through examining the history of the sweater and how the sweater has developed over the years, we find how much significance the patterns hold and how much of Iceland’s own tradition is included in the design of the patterns. After covering the historical part of the research, we take a look at the sweater’s modern adaptations and future prospects, and how the patterns have taken a life of their own through social media. This thesis uses the method of qualitative analysis of literature and an overlook on current blogs and social media websites and is illustrated by pictures from the internet and the writer’s own projects. This thesis focuses on the pattern designs of the sweaters from the point of view of a graphic designer. In conclusions, we find that the patterns do not hold as much importance in defining the sweater as was thought before, but it is rather the material and the structure of the sweater that makes it traditional to Iceland.